Research of Dynamic Characteristic of RV Reducer based on Bond Graph Theory - Liang Quan; Zheng Peng; Zhao Wenhui (Jixie chuandong)
In view of the dynamic characteristic analysis of RV reducer is difficult problems. A simulation model of RV reducer is established based on the theory of power bond graph， the mathematical formula for transmission ratio of RV reducer is deduced， and the simulation modeling method of single transmission loop and complete loop power bond graph of RV reducer is given. By using 20-sim simulation software， the simulation model of RV reducer is analyzed， and the design proposal of RV reducer is given. This method can be used for reference to improve the design level of the reducer.